O estilo em psicanálise: o discurso do analista como arte do bem dizer - Ferreira, Diego Diz [UNESP]; Silva, Rafael Justino da [UNESP]; Mouammar, Christiane Carrijo Eckhardt [UNESP] (FapUNIFESP (SciELO), 2014)
This article circumscribes its problem as concerning the relationship between the aesthetical field and the subjectivation processes; more specifically it aims to analyze the possible stylistic effects of the psychoanalytical discourse on the subjectivity of both speaker and listener. To do so, it takes the analysis of the analyst’s discourse, systemized by Lacan as a strategy to understand the matter of style in psychoanalysis. Unveiling the structure of the analytical discourse, understood as the analyst’s discourse, it is possible to identify that, through style, emerges the possibility of inscription of the object a, as a mark of the real on the symbolical order reigned by loss.

Este artículo circunscribe su problemática a la relación entre la estética y los procesos de subjetivación, más específicamente, objetiva analizar los posibles efectos del estilo del discurso en la subjetividad, tanto del que habla como de quien escucha. Para eso, toma el análisis del discurso analítico sistematizado por Lacan como uma estrategia para la comprensión de la cuestión del estilo en el psicoanálisis. Revelando la estructura, del discurso analítico entendida como discurso del analista, es posible identificar que a través del estilo, surge la posibilidad de inscripción del objeto a, como una señal de lo real en el orden simbólico regido por la falta.

Cet article délimite sa problématique dans la relation entre le champ esthétique et les processus de subjectivation; de manière plus spécifique, cet article a pour objectif d’analyser les possibles effets stylistiques du discours psychanalytique dans la subjectivité, aussi bien par ceux qui le prononce , que de ceux qui l’écoute. De ce fait, l’analyse du discours analytique systématisé par Lacan est considéré comme une stratégie afin de comprendre la question de style en psychanalise. Dévoilant la structure du discours analytique , compris comme le discours de l’annaliste, il est possible d’identifier que par la voie du style, emmerge la possibilité de description de l’objet a, comme une marque de la réalité dans l’ordre symbolique régit par la faute.

O presente artigo circunscreve sua problemática na relação entre campo estético e os processos de subjetivação; de forma mais específica, objetiva analisar os possíveis efeitos estilísticos do discurso psicanalítico na subjetividade, tanto daquele que o pronuncia, como de quem o escuta. Para tanto, toma a análise, discurso do analista sistematizado por Lacan, como estratégia para compreender a questão do estilo em psicanálise. Desvelando a estrutura do discurso analítico, entendido como discurso do analista, é possível identificar que, pela via do estilo, emerge a possibilidade de inscrição do objeto a, como marca do real na ordem simbólica regida pela falta.
The stylistic dimension of psychoanalytic discourse: the art of saying well
El estilo en psicoanalisis: el discurso del analista como arte del bien decir
Keywords: Psychoanalysis; Style; Art of saying well; Object a; Psicoanálisis; Estilo; Arte de bien decir; Objeto a; Psychanalise; Style; Art du bien dire; Objet a; Psicanálise; Estilo; Arte do bem dizer; Objeto a